2014
DOI: 10.3389/fnbeh.2014.00309
|View full text |Cite
|
Sign up to set email alerts
|

Depressive-like behavioral response of adult male rhesus monkeys during routine animal husbandry procedure

Abstract: Social isolation is a major risk factor for the development of depressive illness; yet, no practical nonhuman primate model is available for studying processes involved in this effect. In a first study, we noted that adult male rhesus monkeys housed individually indoors occasionally exhibited a hunched, depressive-like posture. Therefore, Study 2 investigated the occurrence of a hunched posture by adult males brought from outdoor social groups to indoor individual housing. We also scored two other behaviors—ly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
50
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(57 citation statements)
references
References 41 publications
7
50
0
Order By: Relevance
“…The results of this prospective study confirm our earlier observation from retrospective data that adult male rhesus monkeys brought from large outdoor social groups to socially restricted, indoor housing frequently exhibit a depressive-like hunched posture that is very rarely observed in the outdoor social groups (Hennessy et al, 2014). All monkeys of both conditions brought indoors displayed the hunched posture in each round.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…The results of this prospective study confirm our earlier observation from retrospective data that adult male rhesus monkeys brought from large outdoor social groups to socially restricted, indoor housing frequently exhibit a depressive-like hunched posture that is very rarely observed in the outdoor social groups (Hennessy et al, 2014). All monkeys of both conditions brought indoors displayed the hunched posture in each round.…”
Section: Discussionsupporting
confidence: 89%
“…Males were selected for the current experiment because retrospective observations from our previous study suggested that males may be more-sensitive than females to rehousing indoors (Hennessy et al, 2014). Nonetheless, how males and females would differ under the conditions tested here remains unknown and certainly warrants future investigation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Laboratory-housed nonhuman primates may exhibit behavioral depression (Camus et al, 2014; Hennessy et al, 2014; Shively et al, 1997; Shively et al, 2009; Shively et al, 2008; Shively and Willard, 2012) which resembles human depression in physiological, neurobiological, and behavioral characteristics including reduced body mass, hypothalamic-pituitary-adrenal axis perturbations, autonomic dysfunction, increased cardiovascular disease risk, reduced hippocampal volume, altered serotonergic function, decreased activity levels, and increased mortality (Shively and Willard, 2012; Willard and Shively, 2012). Physiological and neurobiological characteristics of monkeys that exhibit behavioral depression have been well characterized (Shively and Willard, 2012) and include dyslipidemia and exacerbated coronary atherosclerosis (Shively et al, 2009; Shively et al, 2008; Shively et al, 2005).…”
Section: Introductionmentioning
confidence: 99%